Study Of True And Fair View Certification By Auditors In Malaysia - Jayalakshmy, Jayalakshmy (2008)
Financial reporting by companies is strengthened with auditors\' report. An auditor\'s report is a statement which communicates his views on the financial statements prepared by the company. When the auditors are satisfied with all the evidences they have verified, they state that the financial statements give a \'true and fair view\'. This research attempts to overcome the limitations pointed out in the earlier researchers by identifying the views of the stakeholders in Malaysia on their acceptability of the concept of \'true and fair\'.